Analysis of legal principles of life safety - Apshai, Fedir; Khalak, Oleh (ScienceRise: Juridical Science, 2021)
This study discusses the legal framework for life safety in Ukraine as of the current year. Ensuring an adequate level of safety at the enterprises of various forms of ownership and directions of the modern economy is a vital task in terms of creating decent working conditions in the country and the development of its economy. The development of the sovereign Ukraine must be accompanied by the creation of a safe state of the environment, economic production, and living conditions to ensure the proper level of human life. The main place in this process is occupied by the legislation in the field of regulation of relations between human health and the environment and safety in emergencies and situations of everyday life, i.e. life safety. The relevance of the subject is conditioned by the need to create an appropriate legal framework for life safety in the country as of its current state. The methodology of this study is based on a combination of a systematic approach to determining the main factors that ensure the establishment of legal foundations for life safety in Ukraine at present and an analytical method of research on a wide scope of issues in this subject area. The main results, obtained during this study, include the identification of the main factors of life safety in modern Ukrainian society and the importance of the legal framework, developed by the state for proper regulation of these issues, as well as the main directions of development of a certain level of life safety culture in modern Ukrainian society. Prospects for further research within the framework of the chosen subject area are conditioned by the need to qualitatively identify the main factors, influencing the process of gradual development of the legal framework for life safety in Ukraine as of its current state and the importance of timely coverage of relevant legal aspects that are vital in modern realities. The applied value of this study lies in the possibility of implementing its main results and conclusions in practice in order to obtain a reliable tool for timely and high-quality determination of the basic legal principles of life safety in Ukraine